2018
DOI: 10.22610/jebs.v10i1(j).2089
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of the 2008 US Financial Crisis: An Intervention Approach

Abstract: The current study investigates the impact of the 2008 US financial crises on the real exchange rate in South Africa. The data used in this empirical analysis is for the period from January 2000 to June 2017. The Seasonal autoregressive integrated moving average (SARIMA) intervention charter was used to carry out the analysis. Results revealed that the financial crises period in South Africa occurred in March 2008 and significantly affected the exchange rate. Hence, the impact pattern was abrupt. Using the SARI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…Additionally, SARIMA model is proposed in this study to serve as a predecessor that is used to filter a time series in order to obtain i.i.d residuals. According to Makatjane et al (2018a), a multiplicative SARIMA model denoted by SARI MA(p, d, q) × (P, D, Q) S follows this mathematical form…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, SARIMA model is proposed in this study to serve as a predecessor that is used to filter a time series in order to obtain i.i.d residuals. According to Makatjane et al (2018a), a multiplicative SARIMA model denoted by SARI MA(p, d, q) × (P, D, Q) S follows this mathematical form…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the estimated Q-statistics also gave vast significant evidence that the estimated model is a white noise process with Pr(Qstatistic = 0.1732)and ε t ∼ i.i.d(0, 0.02978). Makatjane et al (2018a) have suggested that model parameter estimates must be less than one as to deem them to be sufficient and significant.…”
Section: Sarima-ms-egarch-gevd Modelmentioning
confidence: 99%
“…These rates may depend on the money available in the market, existing rates or on the agreement between the institutions. A rise in these rates may cause financial crisis similar to that experienced in 2007 (Bonner & Eijffinger, 2013;Turner, 2013;Saraç & Karagöz, 2016, Makatjane et al, 2018. The short term interest rates are very important for financial stability.…”
Section: Introductionmentioning
confidence: 99%
“…To solve this problem, the SARIMA model can be applied to forecast the selected value if the is non-stationary. Some of the researches regarding the implementation of SARIMA; see Lidiema (2017) and Makatjane et al (2018). In order to integrate the nature of the seasonal pattern within the data, seasonal differencing is applicable to handle seasonal data.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of Lidiema (2017), the model of SARIMA (1,1,0)(0,0,1) is appropriate for forecasting the inflation rates in Kenya. In the case of Makatjane et al (2018), the SARIMA model is implemented to study the impact of the 2008 financial crisis on regarding exchange rate in South Africa.…”
Section: Introductionmentioning
confidence: 99%